The Urgency of Theological Foundations in Islamic Education in the Industry Era 4.0 towards the Society Era 5.0 - Aflisia, Noza; Ahmad E.Q, Nurwadjah; Suhartini, Andewi (International Journal of Education Research and Development, 2021)
Theological foundations in Islamic education are Al-Quran and Hadith. The verses of the Al-Quran and the hadith of the prophet Muhammad have become references for humans in carrying out Islamic education in all eras, times and places. Because Al-Quran rahmatan lil 'alamin is suitable for all eras including the industry era 4.0 towards society era 5.0. Through this article, readers will find theological foundations in Islamic education in the industry era 4.0 towards society era 5.0. It is a very important foundation to know and implement so that the privileges of Islamic education never disappear from civilization. This library research was conducted with use of a variety of references from books, national and international journals that exist to collect data and information. The data collection technique is to conduct a review of the books and journal articles. The data obtained were then processed with data analysis techniques through the stages of collecting data, understanding relevance, analyzing and finding the urgency of the theological foundations. The results of the study reveal that in Al-Quran Allah commands people to read, use reason and do something. In the Hadith, the Prophet Muhammad explained about renewing education, doing ijtihad, humans know more about world affairs, and become useful humans. All of these theological foundations have an urgency in Islamic education to increase faith in Allah, strengthen belief to the Al-Quran and Hadith, strengthen the existence of Islamic education, increase optimism, and encourage creativity in Islamic education.